2017
DOI: 10.31234/osf.io/uzbg6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Concurrent and longitudinal dyadic polynomial regression analyses of Big Five traits and relationship satisfaction: Does similarity matter?

Abstract: Being with a well-matched partner seems essential for a happy relationship. However, past research on personality similarity in couples has reported inconsistent findings. The current study employs a dyadic polynomial regression approach to take into account linear and curvilinear associations between similarity and satisfaction. The concurrent results based on data of 237 couples suggest that beyond actor effects for neuroticism, agreeableness, and conscientiousness and partner effects for agreeableness, simi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
0
16
1
Order By: Relevance
“…Most studies on similarity have assumed linear effects, thereby neglecting the possibilities (a) that too much similarity might be as detrimental for relationship outcomes as too much dissimilarity and (b) that similarity on the low end of a trait dimension has different effects on the relationship as compared to similarity on the high end pole. Indeed, in two recent studies (Weidmann, Schönbrodt, Ledermann, & Grob, 2017;Zhou, Wang, Chen, Zhang, & Zhou, 2017) it was shown that the association between similarity and relationship satisfaction is more complex than previously thought. For instance, in a study with 237 couples, Weidmann et al (2017) observed that couples in which both members had moderate levels of openness were more satisfied with their relationships two years later than couples whose members had similar high or low levels of openness or were dissimilar to each other.…”
Section: Personality and Partner Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on similarity have assumed linear effects, thereby neglecting the possibilities (a) that too much similarity might be as detrimental for relationship outcomes as too much dissimilarity and (b) that similarity on the low end of a trait dimension has different effects on the relationship as compared to similarity on the high end pole. Indeed, in two recent studies (Weidmann, Schönbrodt, Ledermann, & Grob, 2017;Zhou, Wang, Chen, Zhang, & Zhou, 2017) it was shown that the association between similarity and relationship satisfaction is more complex than previously thought. For instance, in a study with 237 couples, Weidmann et al (2017) observed that couples in which both members had moderate levels of openness were more satisfied with their relationships two years later than couples whose members had similar high or low levels of openness or were dissimilar to each other.…”
Section: Personality and Partner Selectionmentioning
confidence: 99%
“…Indeed, in two recent studies (Weidmann, Schönbrodt, Ledermann, & Grob, 2017;Zhou, Wang, Chen, Zhang, & Zhou, 2017) it was shown that the association between similarity and relationship satisfaction is more complex than previously thought. For instance, in a study with 237 couples, Weidmann et al (2017) observed that couples in which both members had moderate levels of openness were more satisfied with their relationships two years later than couples whose members had similar high or low levels of openness or were dissimilar to each other.…”
Section: Personality and Partner Selectionmentioning
confidence: 99%
“…According to Edwards (1994), PRA is useful to more accurately examine the effect of the degree of discrepancy (or congruence and incongruence) between two predictor variables, as compared to the previously widely used difference score approach (Edwards, 2001). Due to its higher precision and validity than this previous approach, the PRA technique is increasingly used in personenvironment fit research and other studies aiming to examine the effect of (in)congruence between two variables and tends to become the actual norm in such research (see Kristof-Brown et al, 2018;Weidmann et al, 2017;Yang et al, 2008). PRA consists in regressing the energy change variable on follower's energy score (b1), leader's energy score (b2), squared follower's energy score (b3), interaction of follower's and leader's energy score (b4), and squared leader's energy score (b5).…”
Section: Analytical Designmentioning
confidence: 99%
“…However, agreeable people are helpful in solving conflicts (Jensen‐Campbell & Graziano, ), empathetic (Graziano, Habashi, Sheese, & Tobin, ), forgiving, and tolerant (Ashton & Lee, ), all of which are characteristics that could be expected to be valued by peers. Supporting this idea, research on romantic relationships shows that people with agreeable partners report higher relationship satisfaction (Leikas, Ilmarinen, Verkasalo, Vartiainen, & Lönnqvist, ; Weidmann, Schönbrodt, Ledermann, & Grob, ) and agreeableness predicts increases in number of friends among university freshmen (Selfhout et al, ). On the other hand, status could also influence development of agreeableness.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroticism could also be relevant for the maintenance of status. Those scoring high on neuroticism experience general insecurity in relationships (Deventer et al, ), their partners are less satisfied (Leikas et al, ; Weidmann et al, ), and they are aggressive towards peers (Tackett, Kushner, Herzhoff, Smack, & Reardon, ), characteristics that point towards potential difficulties in the maintenance of peer relationships. On the other hand, self‐esteem and shyness‐sensitivity, which are both influenced by sociometric status (Reitz et al, ; Yang et al, ), are strongly correlated with neuroticism (Paulhus & Trapnell, ; Robins et al, ), suggesting that sociometric status may also influence neuroticism.…”
Section: Introductionmentioning
confidence: 99%